ANALISIS PERKEMBANGAN DAN ELASTISITAS TRANSMISI HARGA ABALON (HALIOTIS ASININA) DI KABUPATEN BUTON - Mr Endryawan (Quantitative Economics Journal, 2015)
This study aims to analyze the prize development and the price transmission elasticity of abalone in Buton Regency. This study was conducted in June – July 2015 with a survey method. Analysis of price developments and elasticity of price transmission is done by a simple linear regression model. The results showed that each added one period, abalone prices decreased by Rp. 9501 each kilogram. Pricetransmission elasticity show in the level consumers prices has been not fully transmitted to the level of fisherman with vale ofelasticityis 0,11 indicated that when the selling pricein the level consumers increased by 1% then the selling pricein the levelfisherman will increase of 0,11%, or moere easly can be defined that if the selling pricein the level consumers increase, the selling pricein the levelfisherman will also be increase.